Durability of Antiretroviral Therapy Regimens and Determinants for Change in HIV-1-Infected Patients in the TREAT Asia HIV Observational Database (TAHOD-LITE). Issue 2 (February 2018) - Martinez-Vega, Rosario; De La Mata, Nicole L; Kumarasamy, Nagalingeswaran; Ly, Penh Sun; Van Nguyen, Kinh; Merati, Tuti P; Pham, Thi Thanh; Lee, Man Po; Choi, Jun Yong; Ross, Jeremy L; Ng, Oon Tek
Background: The durability of first-line regimen is important to achieve long-term treatment success for the management of HIV infection. Our analysis describes the duration of sequential ART regimens and identifies the determinants leading to treatment change in HIV-positive patients initiating in Asia. Methods: All HIV-positive adult patients initiating first-line ART in 2003–2013, from eight clinical sites among seven countries in Asia. Patient follow-up was to May 2014. Kaplan–Meier curves were used to estimate the time to second-line ART and third-line ART regimen. Factors associated with treatment durability were assessed using Cox proportional hazards model. Results: A total of 16, 962 patients initiated first-line ART. Of these, 4, 336 patients initiated second-line ART over 38, 798 person-years (pys), a crude rate of 11.2 (95% CI 10.8, 11.5) per 100 pys. The probability of being on first-line ART increased from 83.7% (95% CI 82.1, 85.1%) in 2003–2005 to 87.9% (95% CI 87.1, 88.6%) in 2010–2013. Third-line ART was initiated by 1, 135 patients over 8, 078 pys, a crude rate of 14.0 (95% CI 13.3, 14.9) per 100 pys. The probability of continuing second-line ART significantly increased from 64.9% (95% CI 58.5, 70.6%) in 2003–2005 to 86.2% (95% CI 84.7, 87.6%) in 2010–2013. Conclusions: Rates of discontinuation of first- and second-line regimens have decreased over the last decade in Asia. Subsequent regimens were of shorter duration compared to the first-line regimen initiated in the same year period. Lower CD4 + T-cell count and the use of suboptimal regimens were important factors associated with higher risk of treatment switch.